1994
DOI: 10.1126/science.263.5149.935
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Test of Recruitment Limitation in a Coral Reef Fish

Abstract: A long-term, large-scale empirical test of the recruitment limitation hypothesis was done by sampling fish populations from the southern Great Barrier Reef after having monitored their recruitment histories for 9 years. After adjustment for demographic differences, recruitment patterns explained over 90 percent of the spatial variation in abundance of a common damselfish among seven coral reefs. The age structures from individual reefs also preserved major temporal variations in the recruitment signal over at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
272
1
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(280 citation statements)
references
References 44 publications
3
272
1
1
Order By: Relevance
“…Small-scale experiments confirm that juvenile lemon damsels occupying small habitat patches suffer density-dependent mortality (13) within days of settlement (20). In contrast, a large-scale study on the lemon damsel showed that adult abundance on entire reefs increased in direct proportion to the prior density of older juveniles, indicating that mortality of older juveniles and adults was effectively density-independent (21). The large-scale study, although impressive and unparalleled in scope, was not designed to measure mortality in the first days or weeks after settlement, and therefore it cannot be used to ascertain whether density dependence detected in young juvenile lemon damsels scales up.…”
Section: Resultsmentioning
confidence: 95%
“…Small-scale experiments confirm that juvenile lemon damsels occupying small habitat patches suffer density-dependent mortality (13) within days of settlement (20). In contrast, a large-scale study on the lemon damsel showed that adult abundance on entire reefs increased in direct proportion to the prior density of older juveniles, indicating that mortality of older juveniles and adults was effectively density-independent (21). The large-scale study, although impressive and unparalleled in scope, was not designed to measure mortality in the first days or weeks after settlement, and therefore it cannot be used to ascertain whether density dependence detected in young juvenile lemon damsels scales up.…”
Section: Resultsmentioning
confidence: 95%
“…from reef-to-reef). The spatial resolution of management is therefore an important question for reef fish populations, where dispersal plays a central ecological role [26,27]. In these species, adults tend to be associated with particular benthic habitats that are patchily distributed.…”
Section: Introductionmentioning
confidence: 99%
“…The relative importance of presettlement and postsettlement processes in determining species population structures is the subject of debate, but, at least for certain species, recruitment processes can explain a considerable amount of temporal and spatial variation in abundance (Keough and Downes 1982;Doherty and Fowler 1994). However, many benthic invertebrates are very successful at asexual propagation.…”
Section: Discussionmentioning
confidence: 99%
“…Study results are often dependent upon scale and/or the range of habitats being considered (Syms 1995;Eagle et al 2001;Chittaro 2004). Generally, one body of literature supports niche diversification and predicts highly ordered communities (e.g., Connolly et al 2005), while another supports a more stochastic view, highlighting the importance of spatially and temporally variable recruitment of larvae (e.g., Sale and Douglas 1984;Doherty and Fowler 1994). However, with backgrounds of considerable temporal and spatial variability in fish and benthic community structure, many studies support human extraction and alteration of habitat and water quality as determinants of coral reef status (McClanahan 1994;Chapman and Kramer 2001;Halpern and Warner 2002;Graham et al 2006;Pandolfi and Jackson 2006;Maliao et al 2008).…”
Section: Introductionmentioning
confidence: 99%